Differences in Value Systems of Persons with Varying Religious Orientations - Tate, Eugene D. (Journal for the scientific study of religion, 1971)
This study examined possible differences in value systems among persons falling into the four religious orientations identified by Allport and Ross based on the extrinsic-intrinsic distinction. Subjects were members of United Methodist Church groups who voluntarily filled out the Religious Orientation Scale and the Rokeach Value Survey. The findings revealed that three values discriminate between the orientations: the terminal values Salvation and Equality, and the instrumental value Forgiving. The trends in the rankings of values generally supported Allport's theoretical distinctions between the four religious orientations. Ministers participating in the present study varied from those previously studied by Rokeach by ranking the terminal value Equality higher than the terminal value Salvation. This difference was attributed to the fact that the denomination sampled in this study is more liberal than those previously studied by Rokeach.